Geant4 Monte Carlo calculations of gamma- and neutron flux and energy deposition in water outside the PWR 17x17 nuclear fuel assembly BT01 - Jansson, Peter (Uppsala University, 2020)
Using the Geant4 Monte Carlo framework, the flux of radiation emitted from the used nuclear fuel assembly BT01 has been estimated. The emission energy spectra for photons and neutrons calculated using SCALE for this PWR 17x17 fuel assembly were used as source for the radiation transport. The fuel assembly was modelled with the fuel rods emersed in a universe comprised of water. The photon and neutron flux and energy deposition from the source in a plane at the centre of the fuel assembly were calculated.

This dataset contains the raw data files produced by the calculations.

The dataset was originally published in DiVA and moved to SND in 2024.

Med hjälp av Geant4 Monte Carlo-ramverket har strålningsflödet från det använda kärnbränsleelementet BT01 uppskattats. Emissionsenergispektrumen för fotoner och neutroner som beräknats med SCALE för detta PWR 17x17-bränsleelement användes som källa för strålningstransporten. Bränsleelementet modellerades med bränslestavarna nedsänkta i ett universum bestående av vatten. Foton- och neutronflödet samt energidepositionen från källan i ett plan i mitten av bränsleelementet beräknades.

Detta dataset innehåller de rådatafiler som producerades av beräkningarna.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Geant4 Monte Carlo calculations of gamma- and neutron flux and energy deposition in water outside the PWR 17x17 nuclear fuel assembly BT01
Keywords: nuclear fuels; kärnbränslen; gamma radiation; gammastrålning; neutrons; neutroner; Physics with specialization in Applied Nuclear Physics; Fysik med inriktning mot tillämpad kärnfysik; Subatomic Physics; Subatomär fysik